New Research Advances on Marine Invertebrates - Lobo-da-Cunha, Alexandre (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Marine ecosystems encompass a wide variety of invertebrates, including pelagic and benthonic ones, from intertidal to deep-sea habitats in polar and tropical regions. In addition to their high environmental importance, some marine invertebrates also have great economic value. However, despite all of the research that has been conducted so far, much still remains to be learned about these animals. This Special Issue collects articles providing new and relevant information about some marine invertebrates, namely, echinoderms, crustaceans, placozoans, molluscs and annelids. In these articles, a variety of research methods were applied in order to progress our understanding of these marine animals, including light and electron microscopy, liquid chromatography, mass spectrometry, flow cytometry, and cell and tissue cultures.